MSC virtual e-abstract (CPP-04) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Profiling of functional and disability status in locked-in syndrome (lis) patients using international classification of functioning, disability and health (icf) brief core set for stroke in Hospital Rehabilitasi Cheras (HRC). Long term care journey of stroke survivors with mild impairment living in the community: A mixed method research. Hemiplegic migraine, a rare stroke mimic: A case report. More than just sleepiness: A case report on significant hypersomnolence as a ‘not-to-miss’ sign of top of basilar syndrome. Case study: Rehabilitation challenges of a patient with left hemineglect after a right middle cerebral artery territory infarct. Nurse-led activities to increase activity and facilitate recovery amongst individuals with stroke in an inpatient rehabilitation setting. Neurologists versus non-neurologists thrombolysis (nnt) stroke study: Intravenous thrombolytic for adults with acute ischaemic stroke in malaysian primary stroke centres versus acute stroke ready hospitals: comparison of service efficiency and patients' clinical outcomes.